Analyzing spatial hierarchy and its zones for the location of classified hotels in Amman city - Rawashdeh, Akram; Al-Nawaiseh, Samer; Ababneh, Abdulqader (Dirasat: Human and Social Sciences, 2021)
The study aims to analyze the hierarchy of classified hotels in the city of Amman by dividing them into three categories: luxury hotels, business and budget hotels according to the classification adopted by Egan and Neil (2000). The methodology of the study was based on the application of some cartographic techniques and geographic information system. The study found that budget hotels are concentrated in the historical center of the city, while business hotels tend to be dispersed, some of them spread near the range of budget hotels, while others deviate towards the focus points of luxury hotels. As for the luxury hotels were concentrated on the entrances of the historic center of Amman towards the Interior Circle in Shmeisani and the Fifth Circle area in Jabal Amman.